The microvascular extracellular matrix in brains with Alzheimer’s disease neuropathologic change (ADNC) and cerebral amyloid angiopathy (CAA) - Damodarasamy, Mamatha (Fluids Barriers CNS, 2020)
BACKGROUND: The microvasculature (MV) of brains with Alzheimer’s disease neuropathologic change (ADNC) and cerebral amyloid angiopathy (CAA), in the absence of concurrent pathologies (e.g., infarctions, Lewy bodies), is incompletely understood. OBJECTIVE: To analyze microvascular density, diameter and extracellular matrix (ECM) content in association with ADNC and CAA. METHODS: We examined samples of cerebral cortex and isolated brain microvasculature (MV) from subjects with the National Institute on Aging-Alzheimer's Association (NIA-AA) designations of not-, intermediate-, or high ADNC and from subjects with no CAA and moderate-severe CAA. Cases for all groups were selected with no major (territorial) strokes, ≤ 1 microinfarct in screening sections, and no Lewy body pathology. MV density and diameter were measured from cortical brain sections. Levels of basement membrane (BM) ECM components, the protein product of TNF-stimulated gene-6 (TSG-6), and the ubiquitous glycosaminoglycan hyaluronan (HA) were assayed by western blots or HA ELISA of MV lysates. RESULTS: We found no significant changes in MV density or diameter among any of the groups. Levels of BM laminin and collagen IV (col IV) were lower in MV isolated from the high ADNC vs. not-ADNC groups. In contrast, BM laminin was significantly higher in MV from the moderate-severe CAA vs. the no CAA groups. TSG-6 and HA content were higher in the presence of both high ADNC and CAA, whereas levels of BM fibronectin and perlecan were similar among all groups. CONCLUSIONS: Cortical MV density and diameter are not appreciably altered by ADNC or CAA. TSG-6 and HA are increased in both ADNC and CAA, with laminin and col IV decreased in the BM of high ADNC, but laminin increased in moderate-severe CAA. These results show that changes in the ECM occur in AD and CAA, but independently of one another, and likely reflect on the regional functioning of the brain microvasculature.